Factors associated with sleep disorders in adolescents: A Literarture Review - costarin (Journal of health research and technology, 2026)
Objective: This review synthesizes the current global evidence on the causes of sleep disorders in adolescents, identifies key contributing factors, and suggests recommendations for addressing sleep disorders in adolescents. Methods: A literature review was conducted using PubMed, Google Scholar, and ScienceDirect. Studies from 2021–2025 involving adolescents and sleep disorders were selected. The PRISMA guidelines structured the selection process, and data were synthesized narratively. Results: Studies from China, Indonesia, Iran, the USA, and Japan showed mild to severe sleep disorders in adolescents. Factors influencing sleep disorders include: Socio-Ecological Risk and Protective Factors, Generalized Anxiety Disorder, Sleep Hygiene, Physical Condition, Gadget Use. Conclusion: Sleep disorders generally vary based on the severity and type of sleep disorder. Limiting the duration of mobile phone use, anxiety management, using personal protective equipment from pollution, exercise, and reducing the use of sleeping pills are recommended